Indonesian realistic mathematics education learning design for least common multiple material using calendar context for grade VII students - Firsta, Risa Rahmatia; Meryansumayeka, Meryansumayeka; Susanti, Ely; Zulkardi, Zulkardi (Universitas Maritim Raja Ali Haji, 2024)
Students frequently encounter difficulties comprehending and applying the least common multiple (LCM) concepts due to traditional teaching methods lacking engagement and failing to incorporate relevant real-life contexts. Through the Indonesian Realistic Mathematics Education approach, students are expected to be able to solve the problems given related to the Least Common Multiple (LCM) topic and understand it more deeply. This research is design research with a validation study type that includes three main stages: preparing for the experiment, designing an experiment, and retrospective analysis. A literature review and needs analysis were conducted in the preparation stages to identify problems in learning this LCM topic. The design experiment stage involved using activity sheets, which were implemented into teaching and integrated the LCM concept utilizing the context of a calendar. This stage involved data collection through observation, questionnaire, documentation, and field notes. Retrospective analysis was conducted to evaluate the learning design and make revisions based on the evaluation result and feedback from students, teachers, peers, and lecturers. The result showed that using the context of the activity calendar in learning for LCM topics can enhance students’ understanding of the material and make the learning process more contextual and interesting.